Modeling of Marketing Dynamic Capabilities to Increase the Competitive Advantage to the Oil Corporation in Iraq - Almayyahi, Dhulfiqar Ibadi Neemah; Hosseini, Aboalhasan; shirkhodaie, Meysam; movaghar, Morteza (Journal of Ecohumanism, 2024)
This study examines the modelling of marketing dynamic capacities to improve competitive advantage in Iraq's oil companies. In a swiftly changing digital market, firms have considerable obstacles in attaining sustainable competitive advantage (SCA). This research underscores the need to cultivate dynamic capabilities (D.C.) that empower organizations to adjust to market fluctuations and consumer demands. The study identifies essential marketing dynamic capabilities (DMC) characteristics, encompassing customer relationship management, innovative selling tactics, dynamic pricing, strategic marketing management, and brand management. The results indicate a substantial correlation between DMC and competitive advantage, underscoring the imperative for Iraqi oil businesses to utilize these capabilities to succeed in volatile market environments.